Development Of E-Modules In The Basics Of Visual Communication Design Subject For Grade X At Smkn 4 Pinrang - Mustari S. Lamada; Anas Arfandi; Rismayanti (PT. Global Research Collaboration, 2026)
The use of digital learning media in vocational schools is needed to improve the quality of learning in Basic Visual Communication Design (VCD) and to support students’ independent learning. This study aimed to develop an e-module for the Basic VCD subject at SMKN 4 Pinrang and to examine its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included two content experts, two media experts, two instrument experts, a teacher, and Grade 10 students enrolled in the Basic VCD course. Data were collected using content validation sheets, media validation sheets, instrument validation sheets, and a student response questionnaire on the use of the e-module. The results indicated that the e-module was categorized as highly feasible, with validation scores of 100% from content experts and 90.00% from media experts. The practicality test yielded a score of 93.15% (very good), indicating that the e-module was easy to use in learning activities. The effectiveness test showed an N-Gain score of 0.77 (high), with an effectiveness interpretation of 77% (effective), demonstrating that the e-module improved students’ learning outcomes. Therefore, the developed Basic VCD e-module is valid, practical, and effective for use as a learning medium at SMKN 4 Pinrang.